Illustrations of Efficient Solar Driven Organic Reactions - Dinda, Milan; Maiti, Subarna; Samanta, Supravat; K. Ghosh, Pushpito (Current Organic Synthesis, 2016)
The article covers some of the important prior art on solar-mediated organic transformations. It additionally highlights recent initiatives from our laboratory toward use of concentrated solar radiation to drive thermochemical and photo-thermochemical organic reactions. Solar radiation (800-1000 W m-2) comprises a continuum of photons of various wavelengths – from ultraviolet (uv) to visible (vis) to infrared (IR) – covering a part of the electromagnetic spectrum. In the context of organic synthesis, uv-vis radiation helps drive reactions via the excited state of substrate or reagent while IR radiation can provide thermal energy. Single sun exposure limits the photon flux and maximum attainable temperature. On the other hand, concentrated radiation provides higher photon flux and also helps generate higher temperatures. This assists in speeding up reactions and/or conducting reactions at larger scale. A laboratory scale solar photo-thermochemical reactor in V-trough configuration was developed that generated reaction temperatures up to 80 °C besides providing ca. two fold higher photon flux. It was used successfully to conduct a variety of photo-thermochemical bromination reactions in efficient manner. Benzylic bromination of p-methylstyrene-based inter-polymer film was also carried out successfully. Tandem reactions were also developed for the synthesis of more complex molecules such as oxazole derivatives from simple building blocks. The reactions presumably occurred via intermediate formation of halo derivatives. Radiation from parabolic dish concentrators provide still higher levels of concentration of solar radiation. These were used to drive useful thermochemical processes such as the energetically uphill conversion of dicyclopentadiene to cyclopentadiene (Cp) and further downstream processes such as Diels-Alder synthesis of a norbonadiene derivative from Cp. A continuous process of production of β-bromostyrene from cinnamic acid was also explored using radiation from a parabolic trough. Concentrated radiation was additionally employed for distillation of a variety of organic solvents.
Keywords: Solar driven synthesis